ISSUES OF TAXATION IN THE TURKESTAN ASSR (Scientific journal of the Fergana State University, 2023)
This article discusses the tax policy pursued by the Soviet authorities in the early years in Turkestan. The difficult economic situation is analyzed in Samarkand, Osh, Chernyaev, Kazalinsk districts, in mountainous areas.The reasons for the reduced ability of the population to pay taxes, the sharp rise in prices in the markets, the occurrence and causes of famine in Osh and other districts are analyzed. The position of the pastronal population in mountainous areas information based on archival sourses on thesocial state of Turkestan is given, taxation issues, the state of agriculture are highlighted.